The scum villain's self-saving system = Ren zha fanpai zijiu xitong. 2 - Mo, Xiang Tong Xiu (Seven Seas Entertainment, 2022)
Reborn into the world of his favorite trashy web series, Shen Qingqiu, gifted with incredible power and abilities, is destined to be horrifically punished for crimes against half-demon Luo Binghe unless he can get into Binghe's good graces before his rise to power.